Local-Based Adaptive Innovation As A Survival Strategy For Lumajang Batik MSMES - Sumiati, Sumiati; Sudarmiatin; Naswan Harsono; Puji Handayati (Citakonsultindo, 2025)
This study aims to explain how locally-based adaptive innovation has become a survival strategy for Usman Batik Lumajang (UBL) in facing competition from the modern batik industry. Batik MSMEs are required to develop innovations that are rooted in cultural values while also being responsive to market changes. To explore this process in depth, this study uses a qualitative grounded theory method with data collection techniques in the form of in-depth interviews, participatory observation, and documentation. Informants include business owners, craftsmen, marketing staff, consumers, and community leaders. The results of the analysis through open coding, axial coding, and selective coding show that UBL's adaptive innovation is formed from a combination of local cultural values, design creativity, marketing strategy adjustments, and community support. Distinctive motifs such as Pisang Agung and Kuda Kencak are unique resources that are difficult to imitate, in line with the Resource-Based View (RBV) theory. Meanwhile, design development, quality improvement, and product diversification reflect innovation as defined in the OECD (Oslo Manual). The resulting substantive theory concludes that the sustainability of batik MSMEs is largely determined by the ability to integrate local cultural values with modern product innovation in a sustainable manner. Local-based adaptive innovation not only enhances competitiveness but also plays a role in preserving regional cultural identity